Technology-based challenges of informal clinical communication in an Australian tertiary referral hospital: a survey-based assessment of user perspectives - Graeme K Hart; Nicole Hosking; Lorelle Martin; Julia Todd (BMJ Open Quality)
Background Clinical communication failures result in errors, misdiagnosis, inappropriate treatment and poor care. Communication errors contribute to sentinel events and are an underlying factor in healthcare system issues.Formal clinical communication (FCC) tools, such as ISBAR (Identify, Situation, Background, Assessment, Response/Recommendation), improve patient outcomes. FCC governance is focused on electronic medical records (EMRs); however, much informal clinical communication (ICC) occurs outside of the EMR.ICC involves disparate platforms including pagers, SMS texts, encrypted messaging apps, phones and local radio networks. Documentation of ICC in the clinical record is low quality and not easily or routinely audited.Local problem In 2019, our institution commenced a clinical governance assessment of ICC processes against version 2, Australian National Accreditation Standards for clinical communications. Process mapping of ICC indicated a paucity of relevant policy and procedures to govern ICC practices, with highly variable and overly complex processes.Aims To document the technology used in informal communication between clinical and/or administrative staff.To document the self-perceived impact on staff of current communications methods.To document the self-perceived potential efficiency and safety impact of current communications methods.To identify key factors for consideration in organisation-wide informal clinical communication improvement.Method Multidisciplinary online staff cross-sectional survey using Microsoft Forms.Results 115 self-selected clinical and administrative staff completed the survey. Multiple communication channels are used for ICC. Respondents noted high levels of frustration, delay, interruption and inefficiency. Desired communication improvements and use considerations were identified.Conclusions There are gaps in governance standards for ICC. Sequential additions to technology platforms contribute to a high-risk communications environment. Staff perceptions of inefficiency, delay, frustration and a high level of patient safety risk were consistent across professions. This work informed the requirements for a subsequent development of an enterprise platform dedicated to improving ICC.